2022
DOI: 10.3390/s22030749
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Accuracy of Hourly Multi-Output Solar Power Forecast with Physics-Informed Machine Learning

Abstract: Machine Learning (ML)-based methods have been identified as capable of providing up to one day ahead Photovoltaic (PV) power forecasts. In this research, we introduce a generic physical model of a PV system into ML predictors to forecast from one to three days ahead. The only requirement is a basic dataset including power, wind speed and air temperature measurements. Then, these are recombined into physics informed metrics able to capture the operational point of the PV. In this way, the models learn about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…The study [ 64 ] reveals that the output power with the insolation and the air temperature has a linear and nonlinear correlation, correspondingly. Recently, researchers have been more interested in the ML application to increase the accuracy of the forecasters [ 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The study [ 64 ] reveals that the output power with the insolation and the air temperature has a linear and nonlinear correlation, correspondingly. Recently, researchers have been more interested in the ML application to increase the accuracy of the forecasters [ 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
“…Due to forecast power, in [ 69 , 70 ], researchers integrated a PV-performance model into ML methods such as RF, SVR, CNN, LSTM, and hybrid CNN-LSTM. The results indicated that the proposed ML models provide the best performance regardless of the model’s type and forecasting horizon ( Table 7 ).…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
“…To build the dataset, these files were imported, only selecting the interesting metrics, and averaged to obtain 5 min and hourly resolution. Data source location • Institution: Risø DTU National Laboratory for Sustainable Energy • City: Roskilde • Country: Denmark • Latitude and longitude: 55.6867, 12.0985 Data accessibil- ity Repository name: DTU Data Data identification number: https://doi.org/10.11583/DTU.17040767 Direct URL to data: https://data.dtu.dk/articles/dataset/The_SOLETE_dataset/17040767 The SOLETE dataset/17,040,767 Corresponding Reference: [1] Repository name: DTU Data Software release number: https://doi.org/10.11583/DTU.17040626 Direct URL to release: https://github.com/DVPombo/SOLETE The SOLETE platform/17,040,626 Corresponding Reference: [2] Related research articles [3] D. V. Pombo, H. W. Bindner, S. V. Spataru, P. E. Sørensen, & P. Bacher, Increasing the Accuracy of Hourly Multi-Output Solar Power Forecast with Physics-Informed Machine Learning, Sensors 22 (3) (2022) 749. [4] D. V. Pombo, P. Bacher, C. Ziras, H. W. Bindner, S. V. Spataru, & P. E. Sørensen, Benchmarking Physics-Informed Machine Learning-based Short Term PV-Power Forecasting Tools, Under Review.…”
Section: Specifications Tablementioning
confidence: 99%
“… The dataset is complemented by a Git repository [2] including three Python scripts employing only Open Access libraries. The first script simply imports the data, while the second showcases the methodology discussed in [3] and [4] to build physics-informed ML-models for solar power forecasting. This resource is particularly useful for students and researchers first starting in the machine learning-based forecasting field.…”
Section: Value Of the Datamentioning
confidence: 99%
See 1 more Smart Citation